(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
In this article, the authors present literature data on the frequency and structure of causes of hypercorticism in children and adolescents. Based on the analysis of retrospective clinical data for 10 years, it was found that among patients with various forms of hypercorticism in this age period, patients with Itsenko-Cushing’s disease predominated - 26 patients (66.6%), that is, with pituitary microadenomas, compared with patients with Itsenko-Cushing’s syndrome - 4 (10.2%) and other forms of hypercorticism: juvenile dyspituitarism (JD) - 7 (17.9%), obesity with ACTH/cortisol secretion rhythm disorder - 1 (2.5%) and iatrogenic hypercorticism - 1 (2.5%).